Veterinary Histology - Jennings, Ryan; Premanandan, Christopher (Open textbook library., 2017)
Veterinary Histology is a microscopic anatomy textbook focused on domestic species, including the dog, cat, cattle, horses, swine, and camelids. This digital textbook provides comprehensive, system-specific text as well as high-resolution, annotated images along with chapter-specific glossary of terms and learning objectives.